From intertemporal smoothing to intergenerational risk sharing: The effects of different return smoothing mechanisms in life insurance - Alexander Kling; Timon Kramer; Jochen Ruß (European Actuarial Journal, 2025)
In traditional life insurance, typically return smoothing mechanisms are used to reduce the volatility of policyholders' returns and provide risk sharing between policyholders. By analyzing two illustrative smoothing mechanisms, we demonstrate that different smoothing mechanisms may have different effects. We find that mechanisms that are purely based on average historical asset returns can significantly reduce pathwise volatility (intertemporal smoothing) but have hardly any impact on the standard deviation of terminal wealth. In contrast, mechanisms using buffers that are built up "in good years" in order to increase returns "in bad years" can—when properly designed—reduce the standard deviation of terminal wealth without reducing the ex ante expected return by means of intergenerational risk sharing. We conclude that simple generic mechanisms that are often used in academic papers may not fully cover the effects resulting from return smoothing. Our results indicate that—when properly designed—intergenerational risk sharing mechanisms can improve risk-return profiles but at the price of increased complexity and potentially lower surrender values. A strong regulatory focus on simple products and sufficiently high surrender values might disincentivize products with intergenerational risk sharing despite their positive effects.
Keywords: G11; G18; G22; G51; G52; J26; 510; Return Smoothing; Intergenerational Risk Sharing; Participating Life Insurance; Retirement Savings